1996
DOI: 10.1111/j.1447-0756.1996.tb00950.x
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Torsion of a Gravid Horn of a Didelphic Uterus

Abstract: Acute abdominal pain during pregnancy presents a dilemma as signs and symptoms are often modified. Abdominal massage by traditional birth attendants (TBAs') during early labour is a common practice in the rural population, as it is perceived to give a soothening effect to the labouring mother. Many instances of abruptio placentae were reported in the past by this procedure, and in this case, the clinical picture presented as an abruptio placenta. Malpresentation and failure to progress were the indications for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Duplantier et al [5] reported only a case of torsion due to maternal trauma. Achanna et al [6] have reported a case of torsion in uterus didelphys due to abdominal massage during labor by traditional birth attendants. According to Jensen [2] this condition can occur in all age groups, all parity, and all stages of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Duplantier et al [5] reported only a case of torsion due to maternal trauma. Achanna et al [6] have reported a case of torsion in uterus didelphys due to abdominal massage during labor by traditional birth attendants. According to Jensen [2] this condition can occur in all age groups, all parity, and all stages of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The condition is usually associated with pregnancy in the third trimester, and may have been precipitated by the rapid increase in size of the uterus following the placental abruption. Although uterine torsion may give rise to similar symptoms as a concealed placental abruption 3 this case suggests that placental separation and fetal death were the antecedent events. In women who are known to have uterine anomalies who have acute severe abdominal pain in pregnancy, the possibility of uterine torsion should be considered.…”
Section: Discussionmentioning
confidence: 81%
“…Torsion is more common in the presence of uterine fibroids, presumably due to the asymmetrical weight distribution within the uterus. There is a consensus of opinion that the transmission of body movements plays an important part in activating torsion and has been implicated in previously reported cases 3 . Contractions of the abdominal muscles or the degree of filling of the bladder and distension of the intestines are thought to contribute to this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, in the presented case, uterine torsion occurred in the 30th week of gestation and led to neonatal death. The precise etiology is not well known, but presence of uterine myomas, congenital anomalies, pelvic or adnexal masses or adhesions, abnormal fetal presentation, vigorous fetal movements, and abdominal trauma and high-ordered parities account for 70–84% of uterine torsions [ 24 27 ]. As mentioned before, relevant systemic signs and symptoms indicate that connective tissue disorders, most likely Ehlers–Danlos syndrome (EDS), are the only potential leading cause in our patient.…”
Section: Discussionmentioning
confidence: 99%